Effects of Cassava Effluents on the Soil Physicochemical Properties and Water Quality in Ibarapa Region, Oyo State, Southwestern, Nigeria - Oladapo, Samuel; Ogundele, Tunde; Oladipo , Olukayode; Oyedemi , Adeyemo; Aderounmu, Adesoye (International Journal of Environmental Sciences, 2023)
Purpose: This study investigated the effects of cassava effluents on the soil physicochemical properties and water quality in Ibarapa Region Southwestern, Nigeria. Methodology: Three Cassava Processing Sites (CPSs) and Control Sites (CSs) of 5m by 5m quadrant and three wells of varying distances to the CPSs were randomly selected in each of the three local government areas in Ibarapa Region. In all, nine CPSs, nine CSs and nine wells (SPs) were sampled during the dry season. The soil and water samples collected were subjected to laboratory analysis for physicochemical and bacteriological characteristics. The spatial distribution of the CPSs was determined using GIS techniques and Nearest Neighbour Statistic. Findings: The results showed that the CPSs distribution was significantly dispersed. However, that distance to the cassava processing sites impacted on the concentration of parameters tested. Analysis of the soil properties showed that the pH values were higher at the CPSs, elevated values of heavy metals were also noticed and cyanide concentration. Analysis of water quality in some of the sampled wells showed that the water samples were mainly within the WHO permissible standard except higher values recorded for heavy metals in SP 2 and elevated cyanide in SPs 1, 2, 3, 4 and 8 which were in close proximity to the processing sites. Bacteriological analysis also revealed that only SP 2 had the presence of Coliform Escherichia coli. Unique Contribution to Theory, Practice and Policy: The findings alluded to the inherent danger in man's defective interaction with the environment. Hence, the study to a great extent could trigger appropriate measures in soil, water and waste management by stakeholders. Such measure could include treatment of cassava effluents before being dumped in to the environment as well as treating water before being consumed. Governments through her agencies such as the NAFDAC and sanitary inspectors should monitor the activities of these gari, fufu, lafun and tapioca makers especially about the discharge of cassava effluents.